(untitled) (Health Renaissance, 2016)
Background :Head and neck region is a common site for both solid and cystic lesions. The etiology of these masses includes inflammation, congenital-developmental malformations and neoplasia. Thyroglossal cyst, branchial cyst and laryngocoele are the common congenital and acquired conditions. Objective: To assess clinicopathological profile of benign cervico-facial masses in Eastern Nepal. Methods: Patients who were admitted with cervical swellings were included for the study. Acute inflammatory and malignant conditions were excluded. This study was conducted for five years at Department of ENT and Head Neck Surgery, B.P. Koirala Institute of Health Sciences, Dharan, Nepal. Results: Out of total 499 patients included, female were 64.53% and male were 35.47%. Most patients (23%) were from between age 21-30 years. The cervical swellings were most commonly seen in upper lateral neck in 30.46%. Most of the patients (67.13%) presented within 2 years of the appearance of the swelling. Sixty-one percent of the swelling were of the size of 5 cm x 4 cm at presentation. Congenital and developmental malformations were seen in 27.65% Cysts other than developmental were found in 17.02%. The acquired benign lesions were seen in 55.31%.The swelling due to the diseases of the thyroid were found in 38.28%. The most common surgical management was thyroidectomy, done in 38.28%. Conclusion: Benign neck masses are common clinical presentation in the general population in eastern Nepal as in any head and neck clinics all over the world and present a challenge both to the clinician as well as the surgeon. Health Renaissance 2014;12(3): 162-169